2021
DOI: 10.15244/pjoes/129912
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Particulate Matter and Its Correlation with Other Air Pollutants in Xi`an, China

Abstract: IntroductionWith improved living conditions, people gradually pay more and more attention to the problems which were caused by air pollution [1]. The concentrations of particulates and gassy pollutants in the atmosphere were all seriously exceeded. Such as PM 2.5 , PM 10, sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), and ozone (O 3 ) [2]. They would not only lead to a serious decline in atmospheric visibility, but also they would cause many problems to people's travel and transport at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Particles of sizes of 1.0~2.5 µm accounted for about 0.235%, 0.281%, 0.282%, 0.173%, and 0.174%, respectively, with the proportion decreasing by 0.061%. However, the proportion of particles of sizes above 2.5 µm was relatively small; this is consistent with the conclusions given in the literature, which verifies the validity of the results of this paper [22,23]. The changes in the 5 years considered were relatively insignificant for particles of sizes larger than 2.5 µm, but there was still a trend of decreasing concentrations.…”
Section: Quantity Concentrations Of Atmospheric Particlessupporting
confidence: 92%
See 3 more Smart Citations
“…Particles of sizes of 1.0~2.5 µm accounted for about 0.235%, 0.281%, 0.282%, 0.173%, and 0.174%, respectively, with the proportion decreasing by 0.061%. However, the proportion of particles of sizes above 2.5 µm was relatively small; this is consistent with the conclusions given in the literature, which verifies the validity of the results of this paper [22,23]. The changes in the 5 years considered were relatively insignificant for particles of sizes larger than 2.5 µm, but there was still a trend of decreasing concentrations.…”
Section: Quantity Concentrations Of Atmospheric Particlessupporting
confidence: 92%
“…The concentrations in winter were 1.42 times higher than those in spring, 1.63 times higher than those in autumn, and 2.81 times higher than those in summer. Overall, it was observed that the concentrations of particulate matter were the highest in winter and the lowest in summer, which is consistent with the literature [22].…”
Section: Seasonal Concentrations Of Particulate Mattersupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, PM 2.5 in the atmosphere might cause some diseases related to human lung disease, cardiovascular disease, etc. [ 4 , 5 , 6 , 7 , 8 ]. However, people spend as much as 80–90% of their time indoors [ 9 ], and the quality of the indoor environment was the most important to us.…”
Section: Introductionmentioning
confidence: 99%